1999
DOI: 10.1108/01409179910781652
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of stock prices: evidence from the United Kingdom stock market

Abstract: Bio graphi cal NotesDimit rios Tsou ka las and Shomir Sil are both in the School of Man age ment, Pur due Uni ver sity Calu met, Ham mond, IN 42323, USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Based on this theory, graphical disclosures can be explained as a means employed by firms to highlight certain aspects of their performance so that firms can differentiate themselves from less desirable alternatives. A substantial number of theoretical and empirical research supports these arguments about the incentives for voluntary (as opposed to mandatory) information disclosure (see Leftwich, Watts, & Zimmerman, 1981;Verrechia, 1990;Gaeremynck, 1997;Tsoukalas & Sil, 1999;Durukan, 2002;Zeng (2003), Raj & Forsyth, 2004;Deumes & Knechel, 2008;Glover, 2012).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 91%
“…Based on this theory, graphical disclosures can be explained as a means employed by firms to highlight certain aspects of their performance so that firms can differentiate themselves from less desirable alternatives. A substantial number of theoretical and empirical research supports these arguments about the incentives for voluntary (as opposed to mandatory) information disclosure (see Leftwich, Watts, & Zimmerman, 1981;Verrechia, 1990;Gaeremynck, 1997;Tsoukalas & Sil, 1999;Durukan, 2002;Zeng (2003), Raj & Forsyth, 2004;Deumes & Knechel, 2008;Glover, 2012).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 91%
“…It was concluded that earlier results generated by Feldstein (1996) were misleading and by using an appropriate method of time series investigation, it was found that there is no statistical evidence of negative impact of social security on savings. Tsoukalas and Sil (1999) used vector autoregressive approach to explore the relationship between stock return and fundamental variables. Mohan (2006) established relationship between domestic saving and economic growth for various economies with different income levels using Augmented Dicky Fuller (ADF) test (1981), and Granger casuality test (1974).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the study of (Tsoukalas & Sil, 1999), Stock Price Determinants: A Certificate from the British Financial Market, the researchers aimed to determine the extended ability of the ratio for the dividends distributed to the stock market and the profit growth rate in predicting the market prices of traded shares in the British financial market, to serve the purpose of the study, a sample of companies listed in that market for the period 1995 January, 1996 December was studied. The two researchers concluded that dividend distributions are considered the main determinants of stock market prices and that the announcement of distributions increases the market value of shares.…”
Section: Relevant Scholarshipmentioning
confidence: 99%